2016
DOI: 10.1002/fee.1325
|View full text |Cite
|
Sign up to set email alerts
|

Tools and terms for understanding illegal wildlife trade

Abstract: Illegal wildlife trade (IWT) is a global conservation issue that threatens thousands of species, including fish, fungi, medicinal plants, and charismatic mammals. Despite widespread recognition of the problem, debates on the science and policy of IWT generally concentrate on a few high‐profile species (eg rhinoceros, tigers, elephants) and often overlook or conflate complex IWT products, actors, networks, and contexts. A poor understanding of IWT is aggravated by the lack of systematic vocabulary and conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
116
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 49 publications
2
116
1
Order By: Relevance
“…Similar to most conservation debates, the answer is not binary; the extant literature indicates that although legal ivory trading can have a positive impact on the economy without any impact on biodiversity (Cox ; Hirst ), it can also be the link between legal and illegal markets, for example, by providing laundering services to integrate illegal products into the mainstream legal market (Phelps et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to most conservation debates, the answer is not binary; the extant literature indicates that although legal ivory trading can have a positive impact on the economy without any impact on biodiversity (Cox ; Hirst ), it can also be the link between legal and illegal markets, for example, by providing laundering services to integrate illegal products into the mainstream legal market (Phelps et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Failing to understand the drivers of compliance can result in policies that fail to anticipate unintended impacts (Phelps et al. ) or create perverse incentives for additional rule breaking. Stricter wildlife‐use regulations alone are unlikely to guarantee an end to poaching (Challender et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Key informant interviews revealed that women may not engage as often in these activities but when they do it is in specific ways, particularly as intermediaries or consumers (not harvesters or hunters [Phelps et al, 2016]). Participatory mapping activities and focus group discussions also revealed clear differences in knowledge of loris habitat between men and women, likely related to different livelihood activities between these groups in the various focal communities and the times during which they were most likely to see a slow loris.…”
Section: Gendered Knowledge Of Slow Lorisesmentioning
confidence: 99%